Antibiotic sensitivity Pattern of Salmonella Species I1o-laJed by Btood culture in BangabandhuSheikhMujibMedicalUniversity (Bangladesh Journal of Medical Microbiology, 2016)
Typhoid fever occurs in all parts of the world where water supplies and sanitation are sub-standard. Despite the availability of newer antibiotics, emerging antimicrobial resistance has become an increasing problem in the management of Typhoid fever cases. The aim of this study was to determine the antibiotic sensitivity pattern of Salmonella species isolated by blood culture. This was a retrospective study considering the period of January to December 2007  at Bangahandhu Sheikh Mujib Medical University, Shahbag, Dhaka. Blood samples for culture were collected by venepuncture, immediately inoculated into Brain Heart infusion broth and incubated at 370 C. After 24 hours incubation, subcultures were done twice on Blood agar and MacConkeys agar plates. Any growth on the sulrcultured plates were identified by standard microbiological techniques. All of the isolates were then subjected to antibiotic susceptibility test performed by disk diffusion method. A total 2424 specimens of blood collected from patients suspecting of fever, were cultured, out of which 218 (8.99%) were found positive for Salmonella species. In vitro sensitivity test showed that cefixime was highly sensitive (99.41%) followed by  ceftriaxote (97.03%), Azithromycin (83.58%), Ciprofloxacin (67.47%), cefuroxime (73.3%), chloramphenicol (72.62%), co-trimoxazole (69.59%), Amoxicillin (64.33%) and Nalidixic acid (19.26%).  The results call for nationwide surveillance programme to monitor microbial trends and antimicrobial susceptibility pattern of salmonella species in Bangladesh.Bangladesh J Med Microbiol 2008; 02 (02):22-26